Physicochemical And Organoleptic Characteristics Of Flakes Based On Fermented Rice Bran and Beneng Taro Flour (Xanthosoma undipesh K.Koch) - Nia Ariani Putri; Winda Nurtiana; Mohamad Ana Syabana; Bayu Meindrawan; Reizza Muhammad Giyats Al Hisyam Dwi Samara (University of Sultan Ageng Tirtayasa, 2024)
Flakes are a food product and are expected to be able to meet market demand by presenting products that are practical, easy to serve, and fulfill the body's nutritional content. This research aims to determine the level of consumer acceptance of flakes products based on taro beneng flour and fermented rice bran flour by varying the ingredient formulation: taro beneng flour, fermented rice bran flour, rice flour; and the baking time 15 and 20 minutes. The selected treatment will undergo further analysis regarding its physical (color, texture, and rehydration power) and chemical (moisture, ash, fat and crude fiber content) properties. The hedonic test results showed that the sample F1 (45:10:45)% obtained the highest favorability test results in term of color, aroma, taste, texture, and overall attributes. The selected treatments were formulations F1 (45:10:45)% and F2 (40:15:45)% with a baking time of 15 and 20 minutes. The physical characteristic test results include color (lightness 48.80 – 51.70), texture (0.68 – 0.89 N), and rehydration power (47.55 – 85)%; while the chemical characteristic test results include water (2.60 - 4.4)%, ash (2.74 – 3.14)%, fat (19.47 – 22.46)%, and crude fiber (19.78 – 23.06)%.